2013
DOI: 10.1016/j.nano.2013.01.009
|View full text |Cite
|
Sign up to set email alerts
|

An efficient, chemically-defined semisynthetic lipid-adjuvanted nanoparticulate vaccine development system

Abstract: Abstract:A novel vaccine development platform that enables the site--specific conjugation of synthetic lipid adjuvants to recombinant proteins was produced. This technology facilitates the simple and efficient production of homogeneous, chemically--defined, semisynthetic lipoprotein vaccines. Using a polytope 'string--of--beads' approach, a synthetic gene incorporating seven Streptococcus pyogenes M protein strain--specific antigens, and a conserved M protein antigen (J14) was produced, expressed, and attached… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(71 citation statements)
references
References 46 publications
0
71
0
Order By: Relevance
“…For vaccine application, LNPs containing mRNA coding for protein antigens have been used to induce strong immune responses, such as antigen-specific antibody responses and T-cell responses in mice and rhesus macaques [ 18 , 19 ]. In addition, there is increasing evidence of the usefulness of LNPs as efficient antigen-delivery vehicles [ 20 , 21 , 22 , 23 , 24 , 25 ]. For example, by using protein antigens from dengue virus and hepatitis B virus, it has been shown that specific LNPs can enhance co-administered antigen-specific antibody responses, CD4 + T-cell responses, and CD8 + T-cell responses in mice, guinea pigs, and non-human primates without the addition of immunomodulatory adjuvant molecules [ 23 , 24 , 25 ], although the precise mechanism of adjuvanticity of specific LNPs remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…For vaccine application, LNPs containing mRNA coding for protein antigens have been used to induce strong immune responses, such as antigen-specific antibody responses and T-cell responses in mice and rhesus macaques [ 18 , 19 ]. In addition, there is increasing evidence of the usefulness of LNPs as efficient antigen-delivery vehicles [ 20 , 21 , 22 , 23 , 24 , 25 ]. For example, by using protein antigens from dengue virus and hepatitis B virus, it has been shown that specific LNPs can enhance co-administered antigen-specific antibody responses, CD4 + T-cell responses, and CD8 + T-cell responses in mice, guinea pigs, and non-human primates without the addition of immunomodulatory adjuvant molecules [ 23 , 24 , 25 ], although the precise mechanism of adjuvanticity of specific LNPs remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 The concentration used in present study was similar to that previously reported for other peptide-based vaccine evaluation in vivo that utilized J14 as antigen. 21,23,40 Unlike the OVA-Q11 and (NANP) 3 -Q11 conjugates, J14-Q11 was incapable to induce visible b-sheet conformation and unable to form a dense fibrillar network as observed by CD spectroscopy (Fig. 3) and TEM (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…The LCP system has also been applied to the delivery of multiepitope-based polypeptides [102]. A semisynthetic vaccine against G AS was produced by maleimide conjugation of LCP lipidic moiety 5 (see Fig.…”
Section: Lipid-based Self-assembled Nanostructurementioning
confidence: 99%